New Directions in Islamic Education: Pedagogy and Identity Formation By Abdullah Sahin (Markfield: Kube Publishing, 2013. 305 pages.) (American Journal of Islam and Society, 2019)
Abdullah Sahin’s New Directions in Islamic Education offers an original conceptualization of the role of Islamic education in enriching the identity formation of young British Muslims. Existing education literature centered on Muslims is often categorized in one of two ways: (1) texts that offer classical, prophetic depictions of pursuits towards religious knowledge (Al-Attas 1979; Ashraf & Hirst 1994; Abbas 2011); or (2) texts that offer modern representations of the lived experiences of Muslims in western contexts (Abdalla, Chown, & Abdullah 2018; Khan & Siddiqui 2017; Haddad, Senzai, & Smith 2009).